New new thing: how some man you've never heard of just changed your life - Lewis, Michael (London, 1999)
In the last years of the millennium, bestselling author Michael Lewis sets out to find the world's most important technology entrepreneur, the man who embodies the spirit of the coming age. He finds him in Jim Clark, the billionaire who founded Netscape and Silicon Graphics and who now aims to turn the healthcare industry on its head with his new billion-dollar project. Lewis accompanies Clark on the maiden voyage of his vast yacht and, on the sometimes hazardous journey, takes the reader on the ride of a lifetime through a landscape of geeks and billionaires. Through every brilliant anecdote and funny character sketch, Michael Lewis allows us an inside look at the world of the super-rich, whilst drawing a map of free enterprise in the twenty-first century.
Keywords: Entrepreneurship